Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa Kelas V melalui Pendekatan PAKEM di SD Negeri 006 Pangkalan Indarung Kecamatan Singingi - Marhendi, Marhendi (GERAM: Gerakan Aktif Menulis, 2017)
Low learning activity on Math in SDN 006 Pangkalan Indarung Kec. Kuantan Tengah Kab. Kuansing caused the low learning result, which meant the students could not pass the minimum score decided by the school. To improve Math learning activity and the result, Classroom Action Activity research was done by using PAKEM learning. This research was done in two cycles. Every cycle had two meetings with four steps of each meeting, there were planning, proceeding, observing, and reflecting. The data was analyzed by deciding the number and percentage of participated students in every meeting. The result showed that the learning activity and result improved where at the beginning data there were only 7 out of 32 students passed. After the treatment was done, in cycle I the learning result has significant improvement with 21 students (66%) passed, the mean score was 74,4 and in cycle II there were 28 students passed with the mean score was 89,7. In the end of cycle II, there were 30 students brave to ask, 29 students were active to find the learning material, 29 students were creative in giving the idea, 28 students finished the task in time, and 30 students showed their spirit of learning. So, it can be concluded that PAKEM approach can be used to improve students’ learning activity and the result.